Invited Lecture 9: Prospects of immune correction of anti-viral resistance with cryopreserved products of cord blood in coronavirus expansion - Anatoly M Goltsev (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch Academician A. M. Goltsev became the Director of the IPC&C in 2011. Anatoly M. Goltsev is the one who initiated and is the co-author of the researches on development of cryopreservation techniques, long-term preservation and maintenance of the integrity of biological objects of different origins. Academician A.M. Goltsev for the first time proved the possibility of directional change in immunoreactivity of allogeneic bone marrow after cryopreservation with certain modes minimizing an immune conflict in the form of graft-versus-host disease. A. M. Goltsev is the author of over 400 scientific papers, including 4 monographs and 22 patents. For his work, he was awarded many awards like Diploma of the scientific and medical community in Kharkiv (1992), recognised as Soros Professor (1998), V. Ya. Danilevskiy Prize (2002) State Prize of Ukraine in the field of science and technology (2002) the medal of the National Academy of Sciences of Ukraine "For scientific achievement" (2008). The COVID-19 coronavirus pandemic, caused by the SARS-CoV-2 coronavirus, is a global problem today. Existing strategies to overcome the COVID-19 are focused on the use of drugs with direct antiviral action, modulation of the innate immune response, suppression of the "cytokine storm", use of convalescent plasma and more. Importantly, the deregulation of the interaction of innate and adaptive immune systems causes the start of the autoimmune process in the body of the virus carrier, which requires an emphasis on the treatment of such diseases, taking into account the dominant autoimmune component and the use of the drugs with immune suppressive activity, including the cell therapy. Current research shows that drugs based on cord blood (CB) have a versatile potential. The CB contains hematopoietic, mesenchymal stem and differentiated cells (Treg) together with the protein components of plasma, that determines its immunotropic and immunosuppressive properties. Cryobiological techniques (cryopreservation, lyophilization) are mandatory components of long-term storage and use of cell therapy drugs in clinical practice. Experimental studies performed at IPC&C of the National Academy of Sciences of Ukraine have proven the ability of cryopreserved products of CB to prevent the development of viral infection and possible complications caused by it. It was shown that the preliminary introduction of cryopreserved CB leukoconcentrate (cCBLC) prevented the development of influenza in the animals infected with influenza virus (strain A/Victoria/3/75(H3N2)), promoted antiviral antibodies and the formation of the dynamic balance of inflammatory and anti-inflammatory cytokines. The effectiveness of cCBLC is related to the possibility of reprogramming the genes responsible for the implementation of the body's immune responses and induction of "trained" immunity. Such a modification of the immune system state can be the most promising in protecting the body against viruses, in particular COVID-19. Created techniques of cryopreservation of a wide range of cell drugs provide not only their long-term storage but also increase their inherent therapeutic characteristics, which is relevant for their further clinical use. Currently, the results show that cryopreservation and lyophilization stimulate the functional potential of Treg, increasing the immune regulatory properties of lyophilized leukoconcentrate of human CB.